If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8w + 2 = 90 Reorder the terms: 2 + 8w = 90 Solving 2 + 8w = 90 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 8w = 90 + -2 Combine like terms: 2 + -2 = 0 0 + 8w = 90 + -2 8w = 90 + -2 Combine like terms: 90 + -2 = 88 8w = 88 Divide each side by '8'. w = 11 Simplifying w = 11
| 11/h-5=7/5-h | | 68x=y-2875 | | 3x-(3x^2-7x)+8x^2= | | 11p+12=45 | | 2-(13-m)=-(m-19)-6 | | 8k-8=24 | | 1.5a=-12 | | -5.9=w+6.1 | | 9x+-9+9x= | | f(x-3)=5x^2-x-8 | | F(x)=5x^2+6x-8 | | -10.6x+5.6x=40 | | 18x-10-6w=50 | | -5(3d+8)=35 | | -4m+2-4m+12= | | 4(u-9)= | | F(x)=5(90)-100 | | 75=5(x)-100 | | =(3x^3-7x^2+5x-9)-(7x^3-7x^2-4x+4) | | F(x)=5(75)-100 | | 4x-4-7x-10= | | 100=5(x)-100 | | 7U+5U=2U+30 | | F(x)=5(65)-100 | | K(3)=39+-2 | | x-1-Ln(x)=0 | | 16x-19y=24 | | 6x+18-2x+12= | | -4x-9=-21 | | K(t)=13t+-2k(3) | | 3n-44=n | | 8B-11=5-3B |